The noise of time ebook A novel. - Barnes, Julian (2016)
From the bestselling, Booker Prize-winning author of The Sense of an Ending comes an extraordinary fictional portrait of the relentlessly fascinating Russian musician and composer Dmitri Shostakovich and a stunning meditation on the meaning of art and its place in society. • “Brilliant…. As elegantly constructed as a concerto.” —NPR 1936: Dmitri Shostakovich, just thirty years old, reckons with the first of three conversations with power that will irrevocably shape his life. Stalin, hitherto a distant figure, has suddenly denounced the young composer’s latest opera. Certain he will be exiled to Siberia (or, more likely, shot dead on the spot), Shostakovich reflects on his predicament, his personal history, his parents, his daughter—all of those hanging in the balance of his fate. And though a stroke of luck prevents him from becoming yet another casualty of the Great Terror, he will twice more be swept up by the forces of despotism: coerced into praising the Soviet state at a cultural conference in New York in 1948, and finally bullied into joining the Party in 1960. All the while, he is compelled to constantly weigh the specter of power against the integrity of his music.